2008
DOI: 10.1101/lm.1035508
|View full text |Cite
|
Sign up to set email alerts
|

A limited role for the hippocampus in the modulation of novel-object preference by contextual cues

Abstract: Recent evidence suggests that rats require an intact hippocampus in order to recognize familiar objects when they encounter them again in a different context. The two experiments reported here further examined how changes in context affect rats' performance on the novel-object preference (NOP) test of object-recognition memory, and how those effects interact with the effects of HPC damage. Rats with HPC lesions and control rats received NOP testing in either the same context in which they had previously encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 35 publications
6
55
3
Order By: Relevance
“…3B and the 24-h test a day later on the same mice shown in Fig. 3C) revealed a main effect of test [F (1,26) (Fig. 3B).…”
Section: Hdac Inhibition Generates a Type Of Long-term Memory That Pementioning
confidence: 77%
See 2 more Smart Citations
“…3B and the 24-h test a day later on the same mice shown in Fig. 3C) revealed a main effect of test [F (1,26) (Fig. 3B).…”
Section: Hdac Inhibition Generates a Type Of Long-term Memory That Pementioning
confidence: 77%
“…In our previous study, we only examined hippocampal LTP in the cbp KIX/KIX mutant mice (18). The object-recognition experiments we performed in this study may be hippocampus independent because we do not alter object location or the relationship between object and context, both of which have been shown to engage the hippocampus during object recognition (13,25,26). Thus, HDAC inhibition-dependent enhancement in hippocampal LTP may require CBP whereas HDAC inhibition-dependent modulation of long-term memory for object recognition may not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions of the hippocampus cause impairments in a similarly designed task in the monkey (Gaffan and Harrison, 1989) and also in the rat (Bussey et al, 2000(Bussey et al, , 2001. Hippocampal lesions in the rat have also shown that the hippocampus does not contribute to object recognition nor object context memories but only to the spatial location where an object has been previously encountered (Piterkin et al, 2008). An elegant study by Barker et al (2007) have shown that interaction between the perirhinal and medial prefrontal cortices is required in order to solve tasks where association between different forms of memory are required such as the object-in-place task.…”
Section: The Role Of the Perirhinal Cortex In Context And Spatial Memorymentioning
confidence: 99%
“…Indeed, studies with the spontaneous object recognition (SOR) task for rats have implicated PRh in object memory encoding, consolidation, and retrieval (Winters and Bussey, 2005a,b;Barker et al, 2006a,b). The hippocampus (HPC) may also play a role in object recognition, but the specific involvement of this structure remains unclear and may be related to processing of contextual information, rather than object representation per se (Gaffan, 1994;Cassaday and Rawlins, 1997;Bussey and Aggleton, 2002;Mumby et al, 2002;Aggleton and Brown, 2005;O'Brien et al, 2006;Piterkin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%